A Study of Iranian Professional Translators' Attitudes: Its implications for Translator Training - Mohammadi, Ali Mohammad (Iranian Journal of Translation Studies, 2006)
This paper intends to analyze the Iranian translators' attitudes in order to extract the principles and requirements for educational planning of translation within the framework of Richards and Rodgers' (2001) model. This model prepares the ground for a scientific language teaching method which is also applicable to translator training. It includes three stages of approach, design, and procedure. The approach deals with theories and beliefs about the nature of translation and the acquisition of translation competence. The design covers characteristics and kinds of objectives, the selection and sequence of contents, and the role of the teacher and the student. And in the procedure the kind of actual classroom activities and teaching methods are investigated. This paper has analyzed the Iranian translators’ views through retrospection and interview. The results of the study reveal that 97% of the total 34 translators (in this survey) believe that there is a meaningful and positive relationship between the linguistic competence and translation competence. Moreover, 67.41% of them maintain that there is a positive relationship between linguistic performance and translation performance. The nature of the data implies a cause and effect relationship between the variables which should not be ignored in the process of educational planning in translation.